Pengelompokan Serangan DoS pada Honeypot menggunakan Algoritma K-Means - Rendyanto Adi Kurniawan; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
The development of cloud computing technology is one of the fastest growing technologies in the field of processing. Denial of Service (DoS) attacks are one of the main challenges for cloud computing servers because these attacks often occur on cloud computing servers today with various types of DoS attacks. Overcoming attacks on data contained in cloud computing requires a method to detect, prevent advanced threats and trap attacks. One of the suggested methods is using a honeypot. Honeypot is a system that is deliberately made to be attacked and exploited with the aim of being able to retrieve data carried out by attackers. Data mining techniques are the right step to predict and find out the vulnerability to suspicious packets in network traffic based on honeypot activity logs. The suggested clustering algorithm is the k-means algorithm. So based on the problems that occur in cloud computing, this study uses a honeypot that is implemented to be able to retrieve data and three levels of malicious attacks aimed at a cloud computing service called openstack. Honeyd honeypot succeeded in capturing data carried out by attackers when sending three types of DoS attacks, namely TCP Flood Attack, UDP Flood Attack, ICMP Flood Attack with three attack levels of low, medium, and high and with three attack times, namely 5, 10, and 20 minute. Based on the results of the implementation, analysis, and testing of the K-Means algorithm, it can classify three types of attacks and three levels of attack based on the data obtained by the honeypot honeypot.